On the Comparative Complexity of Primitive Recursive Arithmetical and String Functions - Zaslavsky, Igor D.; Khachatryan, Mikayel H. (Mathematical Problems of Computer Science, 2021)
Formal languages LA and LW are introduced as in [1] for the representation of primitive recursive arithmetical and string functions. Shannon functions SHAW and SHWA describing the relations between the complexities of functions representations in these languages are defined as in [1]. A new proof of the upper bounds for SHAW is presented; it is based on a new method giving in some cases new possibilities for applications in comparison with the methods considered in [1].